Adolescent Suicide Risk Behavior - Chaniang, Surachai; Meuangkhwa, Parichart - (Journal of Nursing, Siam University, 2020)
Adolescent suicide risk behavior is a serious public health problem worldwide including Thailand. This study presents an evidences obtained from literature review that is related to adolescent suicide risk behavior and adolescent suicide prevention. To effectively prevent adolescent suicide risk behavior, the program should involve risk reduction and enhance the protective factors by applying three strategies of involving adolescent’s target group: 1) Universal intervention, 2) Selected intervention, and 3) Indicated intervention. The component of adolescent suicide prevention includes emphasizing in each target group the suicide awareness, suicide education, and method of prevention. Some of the preventive methods are peer support, screening techniques, gate keeper training, counselor, care, coping and support training, cognitive behavior therapy, and interpersonal therapy. An empirical findings demonstrated thus far helps to generate a fundamental knowledge for further development of a suicide prevention program for Thai adolescents. Psychiatric-Mental Health Nurses should play a vital role in establishing actions and cooperative working with adolescents, family, school, available health service resources, and community aimed at risk reduction and promoting protective factors that is related to adolescent suicide risk behavior. Keywords: Suicide Risk Behavior, Suicide Prevention, Risk Factor, Protective Factor, Adolescents, Thailand